Variasi Somaklonal dan Penanda Normalitas Pembungaan Pada Kelapa Sawit (Elaeis quineensis Jacq.) - , Diana Larasati G. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Oil palm (Elaeis quineensis Jacq.) is one of the plantation commodities with high economic value in Indonesia. One solution to provide oil palm seed is by doing tissue culture techniques , but occasionally in field it was found abnormality cases up to 5% of the population, especially in the flowering organs. Analysis at the DNA level can be used for early detection. The purpose of this study was to do somaclonal variation detection with specific marker on each stage of in vitro culture in the laboratory with RAPD and microsatellie and after clones planted in the field, morphological identification of abnormal male and female flowers, and determine the influence of environmental factors on palm flowering. The results showed that somaclonal variation begins in the stage of pre nursery and main nursery with fresh explants as a positive control and normality marker on primer OPC-08, OPC-09, OPD-15, SC10-76, SC10-83,OPB-05, W-15, SC10-19. Markers for normal female flowers are primer F1, F5 and M8. Markers for normal male flower are primer F2, primer F3, primer F4, primer F5, primer F6, primer M1, primer M2, primer M4, primer M5, primer M6, primer M7, primer M8, primer M9 and primer M10. Normal and abnormal female flowers can be distinguished by the presence of additional carpel in female flowers whereas normal and abnormal male flowers can be distinguished by the presence of structures such as abnormal carpel in male flowers. Environmental factors affect oil palm flowering.